2017
DOI: 10.1515/atd-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Study Circles in Online Learning Environment in the Spirit of Learning-Centered Approach

Abstract: Abstract:Introduction: In the era of information society and knowledge economy, learning in non-formal environments gets a highlighted role: it can supplement, replace or raise the knowledge and skills gained in the school system to a higher level (Forray & Juhász, 2008), as the so-called "valid" knowledge significantly changes due to the acceleration of development. With the appearance of information technology means and their booming development, the possibilities of gaining information have widened and, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Its basis can be served by a common topic of interest and we analyse this as a learning place of those who want to learn in their free time but cannot meet personally. In the lack of personal presence self-directing gets an even more important role and it is related to the individual responsibility and the self-regulating ability of the individual, while the individual can meet challenges in the online learning environment different from those he got used to in a traditional learning environment (Simándi, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Its basis can be served by a common topic of interest and we analyse this as a learning place of those who want to learn in their free time but cannot meet personally. In the lack of personal presence self-directing gets an even more important role and it is related to the individual responsibility and the self-regulating ability of the individual, while the individual can meet challenges in the online learning environment different from those he got used to in a traditional learning environment (Simándi, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study conducted by Simándi (2017), it was expressed that the online learning environment could be effectively utilized for community learning. Meanwhile, the study by Homoki et al (2023) revealed that most students perceived online education as effective, and it was further noted that students' digital competence showed improvement due to their engagement in online education.…”
Section: Introductionmentioning
confidence: 99%